Development of Environmental Accounting Education through the Implementation of SAK EP-Based Green Accounting - Satsya Yoga Baswara; Dhifah Amaliyah; Eko Nurcahya Dewi; Sufa'ah Hurumun Niam; Afifah Fitri Nuryanti (Economics Education Department Universitas Negeri Semarang, 2025)
This study examines how the implementation of SAK EP-based Green Accounting at BUMDes Istambul Karya contributes to the advancement of environmental accounting education and sustainable village development. Using a descriptive qualitative design and a case study approach, data were obtained through interviews, observations, and document analysis. The findings reveal that although the application of Green Accounting in BUMDes’ financial reporting is not yet fully optimized or standardized in accordance with SAK EP, it provides rich learning opportunities for understanding the integration of environmental costs and ecological responsibilities into accounting practices. Programs such as reforestation, waste management, and ecology-oriented infrastructure enhance environmental carrying capacity, illustrating practical cases for environmental accounting studies. Stakeholder engagement through Pentahelix collaboration—government, business actors, communities, academics, and the media—further supports the educational value of this initiative. Overall, the case demonstrates how community-based financial management can serve as a living laboratory for environmental accounting education.